The Black Sea is Green: What Does Ivan Vazov See Beyond the Outlines of Varna and Burgas? - Rikev, Kamen (Poznańskie Studia Slawistyczne, 2024)
The paper analyzes motives and messages neglected by literary historians in two short travelogues by Bulgarian national poet Ivan Vazov: One of Our Black Sea Pearls (1891) and On the Waves of the Black Sea (1921). The author reassesses the idea of the cities’ ties with Bulgarian tradition, examples of nationalistic attitudes, as well as the persistent approach to mythologizing the national future. The key conclusions are that the texts abound in examples of nationalistic speech; modernization of the two cities is conceived of as a) Europeanisation, and b) as economic development (with particular emphasis on the ports); the two texts reveal Vazov among the first Bulgarian writers to see the role of tourism as a guarantee of prosperity; the writer gives ethnic Bulgarians the wishful role of civilizing colonists; the development of the Black Sea region implies a change in the ethnic structure of the population.